Impact of New-Onset Diabetes after Transplantation on Cardiovascular Risk and Mortality in Korea: A Nationwide Population-Based Study - Seung Shin Park; Bo Kyung Koo; Sanghyun Park; Kyungdo Han; Min Kyong Moon (Diabetes & Metabolism Journal)
Background Limited data are available on the adverse effects of new-onset diabetes after transplantation (NODAT) in solid organ transplantation (TPL) other than kidney. This study aimed to identify the risk of complications associated with NODAT in recipients of kidney, liver, or heart TPL. Methods Using the Korean National Health Insurance Service database, recipients of kidney, liver, or heart TPL between 2009 and 2015 were identified. The incidence of coronary artery disease (CAD), cerebrovascular accident (CVA), and malignancy was compared across groups with NODAT, pretransplant diabetes mellitus (DM), and without DM using Cox regression analysis. Results A total of 9,632 kidney, liver, or heart TPL recipients were included. During the median follow-up of 5.9 years, NODAT independently increased the incidence of CAD (hazard ratio [HR], 2.46; 95% confidence interval [CI], 1.39 to 4.30) and overall mortality (HR, 1.48; 95% CI, 1.14 to 1.95) compared to the reference group even after adjustment for confounders; this was more prominent in kidney TPL than in liver TPL. The risk of CVA was significantly increased by pretransplant DM but not by NODAT in both kidney and liver TPL (HR, 2.47; 95% CI, 1.68 to 3.65; and HR, 3.18; 95% CI, 1.07 to 9.48, respectively). NODAT increased the risk of malignancy in the crude model, which lost its statistical significance after confounder adjustment. Conclusion NODAT independently increases the risk of CAD and mortality after TPL, which is more evident in kidney recipients. There was no additional increased risk of CVA or malignancy with NODAT in solid organ TPL.